2021
DOI: 10.1155/2021/8859579
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Motility and Gut Hormone Secretion in response to Shenhuang Plaster in a Postoperative Ileus Rat Model

Abstract: Postoperative ileus (POI), a gastrointestinal function disorder, is a complication that arises from surgery. Shenhuang plaster (SHP) application to the Shenque acupoint (CV8) to promote the recovery of gastrointestinal function has achieved definite curative effects in clinical settings; however, the underlying pharmacological mechanism remains unknown. In this study, we evaluated the effects of SHP using a Sprague Dawley rat POI model. Then, gastrointestinal transit in different rat groups was evaluated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Early recovery of gastrointestinal function after gastrointestinal surgery is clinically important because it reduces the incidence of postoperative ileus (POI). POI is associated with postoperative pain, increased nausea and vomiting, and increased treatment costs [ 27 ]. This work confirmed that FET in Exp group patients was much shortened compared with the FET in the Ctrl group patients ( P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Early recovery of gastrointestinal function after gastrointestinal surgery is clinically important because it reduces the incidence of postoperative ileus (POI). POI is associated with postoperative pain, increased nausea and vomiting, and increased treatment costs [ 27 ]. This work confirmed that FET in Exp group patients was much shortened compared with the FET in the Ctrl group patients ( P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that a large number of effective schemes are provided for clinical treatment along with vigorous progression research of combination of traditional Chinese medicine and western medicine [ 5 ]. Several formulas, single herb or active ingredient of traditional Chinese medicines, such as Shenhuang plaster [ 6 ], Zingiberis Siccatum Rhizoma [ 7 ], Cistanche deserticola [ 8 ] and hesperidin [ 9 ], had played unique advantages in the treatment of gastrointestinal diseases, whose mechanisms were related to inhibiting inflammatory responses by regulating ghrelin and other intestinal hormones, activating the transient receptor potential A1 (TRPA1) channels in entero-chromaffin cells, stimulating interstitial Cajal cells and stimulating Ca 2+ -dependent myosin phosphorylation. Among them, Da-Cheng-Qi Decoction (DCQD) is a representative laxative prescription with remarkable effect recorded in “Shang Han Lun”, which can effectively improve the inflammatory symptoms of intestinal peristalsis and obstruction, alleviate gastrointestinal paralysis, and improve gastrointestinal motor function with a rapid and highly potent effect [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%